Phenomenon and determinant characteristics of NEET (Not in Employment, Education or Training) youth in matrilineal province - Chintia Anggraini; Werry Darta Taifur; Zulkifli N (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
Economic development positions human as an important factor of production. Therefore quality human resources are needed for sustainable development. Indonesia as a country with a large population potential is expected to take advantage of the opportunity through demographic bonuses that will occur in 2020-2030. However, the emergence of NEET (not in employment, education or training) has become a new problem that threatens the success of development. NEET is a measure that includes young people in the age range of 15-24 years old, who are not in employment, education or training. NEET is considered more comprehensive than unemployment because it can see the dynamics and activeness of youth in the labor market. The presence of NEET is inseparable from the determinant characteristics the chances of someone becoming a NEET youth. This study uses Sakernas data for 2017 and 2018 to see the phenomenon and determinant characteristics of NEET status. The result showed NEET youth in West Sumatera was dominated by economically inactive youth. And by using logistic regression analysis, obtained several characteristic that significantly influence the chance of youth’s vulnerability to become a NEET. Youth who live in rural areas have a greater opportunity to become NEET youth, while youth with high level education are even more vulnerable to becoming NEET. Gender does not have a significant effect on determinants of NEET status in areas that adhere to this matrilineal kinship system. Based on the result of this study, the government as the holder of authority is expected to implement policies to reduce the proportion of NEET youth.